IMPLEMENTATION OF DISTRIBUTION OF HIGH HERITAGE ASSETS TO THE MALE CHILDREN OF THE HEIRS OF STUDY IN SUNGAI JARIANG VILLAGE, BUKITTINGGI - Bunga Mirza Humaira; Masitah Pohan (Inspiring Law Journal, 2025)
The Minangkabau people adhere to a matrilineal kinship system that places high heirlooms as collective inheritance through the maternal line. However, social developments have given rise to changes in inheritance practices, including the granting of high heirlooms to sons, as seen in Sungai Jariang Village, Bukittinggi. This shift has created tension between customary norms, the principle of faraidh, and the needs of modern society. This study aims to analyze the legal validity of high heirlooms, examine the practice of distributing them to sons, and identify obstacles that arise in their implementation. This study is expected to provide an understanding of the dynamics of customary inheritance amidst ongoing social change.            This research uses empirical and descriptive methods to examine the practice of distributing high-ranking heirlooms. Data were obtained through literature review, observation, and interviews. All information was analyzed qualitatively to generate factual understanding and scientific answers to the research questions within the socio-cultural context of the local community at the designated research location.            The status of high inheritance in Sungai Jariang Village remains regulated by Minangkabau custom, which is based on a matrilineal kinship system, even though the community has experienced social dynamics and come into contact with modern law. High inheritance is understood as a symbol of clan identity and a supporter of family continuity, so its management remains under the authority of women in the maternal line and mamak as customary leaders. In practice, sons do not obtain ownership rights to high inheritance, but under certain conditions can be granted use rights based on clan deliberation, especially if the person concerned plays an active role in maintaining or managing the asset. The obstacles to its implementation stem from internal factors in the form of differences in customary understanding and external factors resulting from the influence of social change, which requires efforts to improve understanding of Islamic law and selective adjustment of customary values so that the inheritance system remains relevant without eliminating the basic principles of Minangkabau culture.